The Perception of Budget Managers on The Budget Absorption Variable in New State Universities : (Empirical Studies at University of Pembangunan Nasional “Veteran” Yogyakarta) - Syari’udin, Akhmad; Sutoyo, Sutoyo; Yulianti, Retno (RSF Conference Series: Business, Management and Social Sciences, 2021)
Budget and budget absorption are very important in the sustainability of a budgeting system at state universities. Budget absorption is used as an indicator of performance measurement in a university. The opinion of budget managers is an important factor in efforts to optimize the budget. Therefore, research on the perception of budget managers on the determinants of budget acceptance in state university is very important, especially for new state universities (Perguruan Tinggi Negeri Baru/PTNB), including University of Pembangunan Nasional "Veteran" Yogyakarta (UPNVYK). The purpose of this study is to analyze the variables that affect budget absorption at UPNVYK. The variables are budgeting plan, budgeting management, human resource, procurement of goods dan services (Pengadaan Barang dan Jasa, PBJ), bureaucratic environment, monitoring and evaluation systems, and organizational commitment. This research is expected to formulate recommendations about budget policymaking and its implementation in UPNVYK management in particular and new state universities in general. It is hoped the research will become one of the policy making materials for UPNVYK management on budget implementation from the perception aspect and point of view of managers of the procurement of goods/services.The population of this research is financial management employees in all work units at UPNVYK which consists of 15 work units. The sample of the population is people who have certain positions related to the budget and management of the procurement of goods/services. The method in this study is a qualitative descriptive method. This research data is primary data and secondary data. Secondary data comes from work units and rector regulations at UPNVYK. Primary data using a closed or open questionnaire on the perception of financial management employees at UPNVYK. The result of this research is that the most important issue of budget absorption at UPNVYK is the existence of organizational commitment and commitment from all employees in each unit on various issues related to budget absorption at University of Pembangunan Nasional “Veteran” Yogyakarta.